RELATIONSHIP BETWEEN NUTRITIONAL STATUS, BURN DEGREE, AND TREATMENT WITH BURN INJURY HEALING PROCESS IN PATIENTS AT HOSPITAL IN MEDAN CITY, INDONESIA - impolmudesta - munthe; Dewi Eliza Diani Suza; Asrizal Asrizal (International Journal of Nursing and Health Services (IJNHS), 2019)
The burn is a type of tissue damage or injury caused by contact with very high-temperature substances (for instance: fire, hot water, chemical element, electricity, and radiation) or deficient substances. Burn healing can be done by giving proper burn treatment and observing patient nutritional status. The study aimed to examine the relationship between nutritional status, burn degree, and wound treatment towards burn healing process in patients with burn injury at two public hospitals in Medan City. It was a quantitative study with correlational design. The research samples comprised of patients with second-degree burn (Grade II) and third-degree burn (Grade III), with the total number of participants was 45 who were selected through accidental sampling technique. By employing Pearson statistical calculation, it was obtained that the p-value was <0.005 on nutritional status, burn degree, and burn to heal. Based on logistic regression analysis, it was obtained that the order of factors that affected the burn healing process from the most to the least dominant one was nutritional status, burn treatment, and burn degree. This study also found that there was a significant correlation between nutritional status, burn degree, and burn treatment toward burn healing. Therefore, it is suggested that health practitioners could be mindful of patients' nutritional status, burn degree, and burn treatment to accelerate the burn healing process. Keywords: burn, nutritional status, burn degree, burn treatment, and burn healing process